Seeds 2 : supporting women's work around the world - Leonard, Ann, 1945-; Chen, Martha Alter; Buvinic, Mayra; Elias, Misrak; Jahan, Rounaq; Moser, Caroline (Originally published in a pamphlet series Seeds., 1995)
Africa; Asia; North America; International; Afterwords.